Effects of crude oil on Macrobrachium rosenbergii(De Man) egg hatchability under different pH levels - Wong Yip Hing (Terengganu: Universiti Putra Malaysia Terengganu, 2014)
The hatching rate of Macrobrachium rosenbergii eggs in various pH was studied by using an innovated flow through bioassay technique. This bioassay method relies on the fact that M. rosenbergii fertilized eggs when detached from the mother prawn were able to hatch artificially.